Uncertainty and bank wholesale funding - Valeriya Dinger; Ben Craig (Deutsche Bundesbank, 2013)
In this paper we relate a bank's choice between retail and wholesale liabilities to real economic uncertainty and the resulting volatility of bank loan volumes. We argue that since the volume of retail deposits is slow and costly to adjust to shocks in the volume of bank assets, banks facing more intense uncertainty and more volatile loan demand tend to employ more wholesale liabilities rather than retail deposits. We empirically confirm this argument using a unique dataset constructed from the weekly reports of the 122 largest U.S. commercial banks. The high frequency of the data allows us to employ dynamic identification schemes. Given the evidence presented in this paper we argue that regulatory measures targeting a cap on wholesale funding would limit funding uncertainty but will increase the exposure to asset-side shocks.
Keywords: G21; E44; 330; wholesale funding; retail deposits; bank uncertainty; loan volume volatility